ANALISIS KETERKAITAN ANTAR INDUSTRI DAN SEKTOR KUNCI DI INDONESIA - Soedomo, R Pramono (Badan kebijakan Fiskal, 2010)
The industrial sector plays an important role in the development of the Indonesian economy. The problem of mapping types need anything from 175 industry sectors that have a relationship with each other linkages that need to diprioritas to increase in domestic industrial sector. This study aims to map and analyze the inter-industry linkages and key sectors in Indonesia. To view the analysis of linkage and multiplier analysis in this study using input-output model with the 10-year 2005 data tables 175 sector classification. Linkages among sectors using methods known forward and backward linkage index linkages. Determine the index number of key sectors is a priority sector.From the analysis results can be seen that there are 20 key sectors in Indonesia, the sector: (1) pulp, (2) oil industry of animal and vegetable oils, (3] skin equalize, and preparations, (4) rice industry (5) industrial sugar, (6) basic metal industries rather than iron, (7) animal feed industry, [8] service restaurant, (9) entertainment services, recreation and cultural services, private [10] of meat offal and the like, (11] textile industry, (12] electricity and gas, (13] residential buildings and non residence, (14] and mounted industrial sawn timber, (15] highway transportation services, (16] roads, bridges and ports, (17] poultry and results -result, (18] fertilizer industry, (19] Manufacture of paper and paperboard and (20] marine transportation services. With the 20 key sectors, we can know these sectors have forward and backward linkages are high. For that government policy should be more focused on the 20 key sectors.